Single cell sequencing reveals that CD39 inhibition mediates changes to the tumor microenvironment - Lilong Liu; Yaxin Hou; Changqi Deng; Zhen Tao; Zhaohui Chen; Junyi Hu; Ke Chen (Nature Communications, 2022)
The molecular mechanisms underlying tumour heterogeneity in bladder cancer remain to be explored. Here, the authors perform single cell RNA sequencing and identify CD39 as a potential target for immunotherapy, which they validate in vivo.